Private Blockchain-Driven Digital Evidence Management Systems: A Collaborative Mining and NFT-Based Framework - Butrus Mbimbi; David Murray; Michael Wilson (Information)
Secure Digital Evidence Management Systems (DEMSs) ae crucial for law enforcement agencies, because traditional systems are prone to tampering and unauthorised access. Blockchain technology, particularly private blockchains, offers a solution by providing a centralised and tamper-proof system. This study proposes a private blockchain using Proof of Work (PoW) to securely manage digital evidence. Miners are assigned specific nonce ranges to accelerate the mining process, called collaborative mining, to enhance the scalability challenges in DEMSs. Transaction data includes digital evidence to generate a Non-Fungible Token (NFT). Miners use NFTs to solve the puzzle according to the assigned difficulty level d, so as to generate a hash using SHA-256 and add it to the ledger. Users can verify the integrity and authenticity of records by re-generating the hash and comparing it with the one stored in the ledger. Our results show that the data was verified with 100% precision. The mining time was <semantics>2.5</semantics> s, and the nonce iterations were as high as <semantics>80×103</semantics> for <semantics>d=5</semantics>. This approach improves the scalability and integrity of digital evidence management by reducing the overall mining time.